Wearable programming for the active lifestyle using Garmin Connect IQ - Jepson, Brian 1967- (O'Reilly Media, 2016)
If you want to design apps for smart watches, it's important to know that different platforms have vastly different capabilities. Apple Watch and Android Wear, for instance, serve primarily as smartphone extensions with fast CPUs, bright displays, and relatively short battery life. Pebble's watches improve on this with better battery life and screens that work outdoors. Garmin watches take battery life and durability a step further. It's said that if you know how to build a boat, you can build things that will stand up to any environment this planet can throw at you. The "boatbuilders" at Garmin have created watches for long-term use in punishing, sometimes extreme conditions (such as a 24-hour ultra marathon). In this report, author Brian Jepson takes you on a hands-on tour of Garmin and its Connect IQ SDK. Garmin goes furthest in prioritizing run time and resilience over raw processing power, but as you'll discover, the watch does not sacrifice the functionality you need to develop first-class fitness- and health-related applications. This report explores both the advantages and constraints of working with Connect IQ. Explore Garmin's ability to collect data from users and return timely results to them Start developing for Connect IQ by using templates for four kinds of apps Work with example projects in Connect IQ, including ways to read data from an ANT+ sensor Get developer resources for building wearable apps that do more with less Brian Jepson is an O'Reilly editor, hacker, and co-organizer of Providence Geeks and the Rhode Island Mini Maker Faire. He's also a geek-at-large for AS220, a non-profit arts center in Providence, Rhode Island. AS220 gives Rhode Island artists uncensored and unjuried forums for their work and provides galleries, performance space, fabrication facilities, and live/work space
Includes bibliographical references. - Online resource; title from title page (Safari, viewed December 6, 2018)
Keywords: Wearable computers; Mobile apps; Application software -- Development; Application program interfaces (Computer software); Ordinateurs-vêtements; Applications mobiles; Logiciels d'application; Développement; Interfaces de programmation d'applications; APIs (interfaces); Application software; Development